ANALISIS KUALITAS PELAYANAN PUBLIK DALAM PEMBUATAN SURAT IZIN GANGGUAN (HO) DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PEKANBARU (Study Kasus : Usaha Cucian Mobil Di Kecamatan Bukit Raya) - Dini Indah Vionica; Nurmasari Nurmasari (UIR Press, 2018)
This study aims to know and analyze the strategy of the General Election Commission in increasing the participation of Pemilih Pemula Pemilihan Dumai Mayor and Vice Mayor in Dumai Barat District in 2015. Strategic indicators in increasing Pemilih Pemilih participation include vision, mission, goals, targets, policies, programs, activities. This type of research is descriptive survey. The method used is quantitative method, which is prioritize the list of questionnaires, observation, interviews as a means of data collection. Population and sample in this research is intended for Chairman, Secretary of KPU, member of commissioner and staff of KPU Secretariat of Dumai City, as well as voting society of West Dumai District. The sampling technique used is purvosive sampling. Primary data include data on strategic of General Election Commission in increasing Pemilih Pemilih Beginner at Dumai Mayor and Vice Mayor Election in Dumai Barat Sub-district 2015, collected by questionnaire questionnaire technique, observation, interview. Data that can be obtained, processed by means of frequency table. Based on the analysis, the researcher concludes that the General Election Commission's strategy in increasing the participation of the newly elected voters in the Mayor and Vice Mayor of Dumai in Dumai Barat Sub-district 2015, which is seen from the above indicator of the most number of 40 with good category strategy, it can be proven from seven indicators of vision strategy, mission, goals, objectives, policies, programs, and activities, almost all of the indicators are in fairly good category. Recommendations to consider in order to improve the KPU's strategy need to be trained for KPU officers for the socialization team in the novice voter community so that the officers have a creative strategy. Need socialization and supervision of SOP to be followed and followed. Commitment of KPU officers to rule management is required.